Ecotoxicologia da água de um trecho do rio são francisco verdadeiro - Johann, Adriana da Silva Tronco (2015)
Environmental impacts have become a reality ever more present in aquatic ecosystems, suffering changes in the constitution of the chemical elements of water, availability and their nutrient dynamics. Therefore, comprehensive methodologies are needed to assess the actual condition of these ecosystems, following their changes. In this sense, the objective of this study was to evaluate the water quality of the basin of the São Francisco Verdadeiro river, by analyzing the physical, chemical, microbiological variables, and acute and chronic toxicity tests with the test organism Daphnia magna, to identify possible natural or anthropogenic interference. Thus, fortnightly collections were carried out in six sampling locations (P1, P2, P3, P4, P5 and P6), on the period from April 2013 to April 2014, totalizing 143 samples, of which 31 water quality variables were evaluated, with subsequent calculation of the Water Quality Index (WQI), and acute and chronic toxicity tests. The results obtained for the physical, chemical and microbiological variables showed that dissolved oxygen (Sites P3, P5 and P6), turbidity and ammonia nitrogen (Site P6), pH, biochemical oxygen demand, total phosphorus, fecal coliform bacteria (Escherichia-coli), cadmium, lead, manganese, nickel and zinc (All locations), presented different values of the limits recommended by CONAMA resolution No 357/2005, for Class II waters. It is noteworthy that such disagreements have occurred at different times. WQI values ranged from good to great quality, despite high values of some variables. For acute tests, the results showed no toxic effect on any of the sites sampled throughout the study period. For acute tests, the results showed no toxic effect on any of the evaluated sites throughout the study period. With regard to chronic tests, toxic effect occurred in 5.59% of the samples for the parameter longevity, observed by the death of Daphnia magna organisms during the test, and 97.90% of the samples for fertility parameter, verified by the reduction in reproduction, in which the samples showed a reduced number of offspring compared to the control (M4 culture medium). Toxic effect events registered for fertility were compared with pH the variables, total phosphorus, BOD, fecal coliforms, cadmium, lead, copper, nickel and zinc, which presented different values of the limits established legislation by CONAMA Nº 357/2005, for water class II, since it was observed that the toxic effect events, often coincided with at least one variable above the limits. Therefore, the results obtained for the physical, chemical and microbiological variables showed that the São Francisco Verdadeiro river is impacted by the use and occupation of the basin; receiving contributions of rural and urban áreas, and chronic toxicity tests indicated inadequate conditions for the protection of aquatic life, showing that they are effective tools for assessing a body of water, can serve as allies of the classic valuation methods.